Analisis Kinerja Keuangan pada PT.Ace Hardware Indonesia Tbk - Nur Qomariah; Alwi Alwi (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2021)
This study aims to analyze the financial performance of Pt Ace Hardware Indonesia Tbk using the ratio of Return on Assets, Return on Equity, Net Profit Margin, and Gross Profit Margin. This type of research is descriptive using quantitative data from secondary data sources. The research instrument used is the income statement and financial position report for 10 years from 2010-2019. The population used is the financial report notes of Pt Ace Hardware Indonesia tbk 13 years from 2007-2019 and the research sample for 10 years from 2010-2019 with the sampling used is purposive sampling. The data analysis technique used descriptive per component analysis. In this study, data analysis of one-party t-test (One Sample t-test) was also used. The results showed that: T_count for Return on Asset (ROA), Return on Equity (ROE), Net Profit Margin (NPM) is smaller than t table so it states that Return on Asset (ROA), Return on Equity (ROE), Net Profit Margin (NPM) ) on bad Pt.Ace Hardware Indonesia Tbk. Whereas for T, the Gross Profit Margin is greater than the t table, so it states that the Gross Profit Margin at Pt Ace Hardware Indonesia Tbk is healthy.